Clinical and Epidemiological Characterization of Patients Diagnosed with Cerebrovascular Disease at the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos - Roberto Castellanos Hernández; Amanda Avello Rodríguez; Tomás Castillo Juiz (Revista Finlay)
Foundation: cerebrovascular diseases are among the leading causes of death worldwide and have a significant social impact.  Objective: to characterize patients diagnosed with cerebrovascular disease admitted to the neurology ward of Cienfuegos General Hospital from a clinical and epidemiological perspective.  Methods: a descriptive, cross-sectional study was conducted between January and December 2023, with a total of 778 patients admitted to the neurology ward of Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos province with a discharge diagnosis of cerebrovascular disease. Data were obtained from the statistics department records and processed in Excel and SPSS version 26. Sociodemographic and clinical variables were analyzed primarily. Descriptive statistical methods such as frequency and percentage calculations, as well as measures of central tendency and dispersion and incidence rates, will be applied.  Results: males predominated (58.4 %), and the mean age was 68.6 years. The most frequently associated conditions were high blood pressure (12.8 %) and pneumonia (4.0 %). February was the month with the highest number of cases (79, 10.2 %), and there did not appear to be a stationary trend. The mean length of stay was 7.8 days. The most frequent type of stroke was atherothrombotic (292, 37.8 %). A case fatality rate of 19.7 % was reported. A significant association was found between hemorrhagic stroke and higher case fatality.  Conclusions: the disease presented a typical pattern in epidemiological variables. Ischemic stroke occurred more frequently, while hemorrhagic stroke was associated with higher case fatality.